MARKET SEGMENTATION ANALYSIS IN FOOD SELECTION - Muhamad Stiadi (SEAN Institute, 2022)
This study aims to identify and analyze the market segment of food selection for students of the management study program at Universitas Sembilanbelas November Kolaka. The number of samples in this study were 75 student respondents. Some of the variables used in this study include health, sensory appeal, price, weight control, familiarity, food, convenience, natural content, food restriction. In this research, an analytical tool is used, namely the K-Mean Cluster. The results of this research show that there are three segments. the first segment is respondents who do not show dominant variables in certain variables, the second segment is respondents who attach importance to sensory appeal, price, weight control, familiarity, mood, convenience, natural content attributes, the third segment is respondents who attach importance to health attributes.